Assessment of peripartum psychological disturbances in relation to modes of delivery - Radeef, Ali S; Al-Kubaisi, Muna Kh; John, Akbar B; AI, Nur Khairulnisa (UI Scholars Hub, 2019)
Background: Anxiety disorders are common during peripartum period. This study aimed to identify which mode of delivery was more prone to develop psychological disturbances. Methods: This prospective cohort study conducted among 541 pregnant women presented for spontaneous labour, induction or elective caesarean section in a Malaysian hospital. The severity of depression, anxiety and stress symptoms are assessed by using self-rated depression anxiety and stress scales in four different occasions; pre-labour/operation, 24 hours postnatal, 2 weeks, and at 6 weeks. Results: In the prenatal period, there was no statistically significant difference in the mean score of depression between women coming for labour (4.17±5.28) and elective CS (4.21±5.87). During puerperium; at 24 hours postnatal, 2 weeks and 6 weeks assessments there was no significant difference in depression score among patients with different modes of delivery. The overall scores were (4.23±5.46, 3.26±4.85, 0.78±2.37, 0.18±0.93) for patients going through vaginal delivery, instrumentation, emergency or elective CS. The same trend was found when anxiety and stress were analysed. Conclusions: The most prominent peripartum psychological disturbances symptom is anxiety. Minority of patients will experience persistence anxiety by the end of 6 weeks postpartum. The caesarean section and induction of labour does not increase the psychological impact.